2018
DOI: 10.1038/s41467-018-07037-9
|View full text |Cite
|
Sign up to set email alerts
|

Membrane association and remodeling by intraflagellar transport protein IFT172

Abstract: The cilium is an organelle used for motility and cellular signaling. Intraflagellar transport (IFT) is a process to move ciliary building blocks and signaling components into the cilium. How IFT controls the movement of ciliary components is currently poorly understood. IFT172 is the largest IFT subunit essential for ciliogenesis. Due to its large size, the characterization of IFT172 has been challenging. Using giant unilamellar vesicles (GUVs), we show that IFT172 is a membrane-interacting protein with the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 57 publications
(72 reference statements)
0
27
0
Order By: Relevance
“…Additionally, it was shown that the ubiquitination machinery is present in the flagella of Chlamydomonas [ 134 ] and that components of the IFT machinery interact with ubiquitinated proteins such as α-tubulin during cilia disassembly [ 135 ]. Furthermore, molecular genetics studies suggest that the membrane-associated IFT subunit IFT172 is also important for dynein-2 targeting or turnaround at the ciliary tip by an unknown mechanism that likely involves the Chlamydomonas microtubule end binding protein 1 [ 136 139 ]. Interestingly, IFT172 predominantly co-immunoprecipitates a version of the dynein-2 heavy chain that is somewhat larger in molecular mass suggesting that it could be modified, perhaps by ubiquitination [ 124 ].…”
Section: Intraflagellar Transport On Doublet Microtubulesmentioning
confidence: 99%
“…Additionally, it was shown that the ubiquitination machinery is present in the flagella of Chlamydomonas [ 134 ] and that components of the IFT machinery interact with ubiquitinated proteins such as α-tubulin during cilia disassembly [ 135 ]. Furthermore, molecular genetics studies suggest that the membrane-associated IFT subunit IFT172 is also important for dynein-2 targeting or turnaround at the ciliary tip by an unknown mechanism that likely involves the Chlamydomonas microtubule end binding protein 1 [ 136 139 ]. Interestingly, IFT172 predominantly co-immunoprecipitates a version of the dynein-2 heavy chain that is somewhat larger in molecular mass suggesting that it could be modified, perhaps by ubiquitination [ 124 ].…”
Section: Intraflagellar Transport On Doublet Microtubulesmentioning
confidence: 99%
“…While undertaking this work, a crystal structure for IFT80 was published highlighting that while it had the same domain organization, IFT80 adopted an altered 3D configuration of the second - propeller domain from β ′-COP and also formed a dimer unlike the triskelion COP I cage (Taschner et al, 2018) . However, while not a solved structure, purified IFT172 adopted two configurations by negative stain electron microscopy (EM) when incubated with and without lipids, the former being mutually restrictive with IFT57 binding (Wang et al, 2018) . However, respecting the limitations of homology modeling without solved structures, we found 4 IFT-A proteins (IFT144, IFT140, IFT122, and IFT121) have very high sequence and structural similarity to COPI a and β ′ subunits with N-terminal WD40 repeats and C-terminus TPR region ( Figure 6B ).…”
Section: Resultsmentioning
confidence: 99%
“…As secretory events occur at the ciliary tip via budding and IFT172 can bend membranes, it is also unclear whether the parking of IFT172 at the tip is involved in these secretory events through changing the local curvature of the ciliary tip membrane. Immunofluorescence localization results revealed that large foci of IFT172 could be observed around the mother centriole at the initiation stage of ciliogenesis, implying that IFT172-lipid association may be present in the entire cilium structure (Wang et al, 2018).…”
Section: Ift172 and Vesicular Traffickingmentioning
confidence: 95%
“…the giant unilamellar vesicles in vitro (Wang et al, 2018). In addition to IFT172, other IFT subunits also possess a membraneassociated function during ciliogenesis.…”
Section: Intraflagellar Transportmentioning
confidence: 97%